Action of three bioavailable antioxidants in orbital fibroblasts from patients with Graves’ orbitopathy (GO): a new frontier for GO treatment? - Rotondo Dottore, G.; Ionni, I.; Menconi, F.; Casini, G.; Sellari-Franceschini, S.; Nardi, M.; Vitti, P.; Marcocci, C.; Marinò, M. (Journal of endocrinological investigation, 2018)
Objective Oxidative stress is involved in the pathogenesis of Graves’ orbitopathy (GO) and an antioxidant approach has been advocated for GO treatment. Here, we investigated the action of three antioxidants in orbital fibroblasts, namely, vitamin C, N -acetyl- l -cysteine, and melatonin. Methods Primary cultures of orbital fibroblasts from six GO patients and six control subjects were established. Cells were treated with H 2 O 2 to induce oxidative stress. Cell vitality assays were performed to determine the non-cytotoxic dose of each antioxidant. The following assays were performed: glutathione disulfide (GSSG), as a measure of oxidative stress, cell proliferation, hyaluronic acid (HA), TNFα, IFNγ, and IL1β. Results H 2 O 2 induced oxidative stress (augmented GSSG), increased cell proliferation as well as cytokine release, but did not affect HA release. All of the three antioxidant substances reduced H 2 O 2 -dependent oxidative stress. Vitamin C reduced proliferation in GO, but not in control fibroblasts. N -acetyl- l -cysteine reduced proliferation and IFNγ in GO, and HA and IL1β in both GO and control fibroblasts. Melatonin reduced IL1β and HA in GO and control fibroblasts, and IFNγ only in GO fibroblasts. Conclusions Our study provides evidence in support of an antioxidant role of vitamin C, N -acetyl- l -cysteine and melatonin in orbital fibroblasts. Some of the effects of these compounds are exclusive to GO fibroblasts, whereas some other are observed also in control fibroblasts. Our observations provide a basis for a possible clinical use of these substances in patients with GO.